Answer:
-8 ≤ y ≤ 8
Step-by-step explanation:
Subtract 7 from the first one:
y ≥ -8
Subtract 3 from the second one, then multiply by 4.
y/4 ≤ 2
y ≤ 8
Now, you can write these as a compound inequality:
-8 ≤ y ≤ 8
_____
<em>Additional comment</em>
You basically solve these the same way you would an equation. The only difference is that multiplying or dividing by a negative number will reverse the inequality symbol:
2 > 1
-2 < -1 . . . . . multiplied above by -1.
Answer:
$175
Step-by-step explanation:
3.5 x 50 = $175
The equation x² − 10x − 11 = 0 that is equivalent to (x – 5)² = 36. Then the correct option is A.
<h3>What is an equivalent expression?</h3>
The equivalent is the expressions that are in different forms but are equal to the same value.
The equation is given below.
x² − 10x − 11 = 0
Then the equation can be written as
x² − 10x + 25 – 25 − 11 = 0
(x – 5)² = 36
Then the correct option is A.
The complete question is attached below.
More about the equivalent link is given below.
brainly.com/question/889935
#SPJ1
Answer:
Step-by-step explanation:
Percentile Formula
P = (n/N) × 100
Where,
n = ordinal rank of the given value or value below the number
N = number of values in the data set
P = percentile
Or
Percentile = (Number of Values Below “x” / Total Number of Values) × 100